Estimation of Parameters of Homogeneous Gaussian Random Fields - Kozachenko, Yu. V.; Kurchenko, О. O. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
On the basis of the limit theorem for quadratic variation, we construct a consistent estimator for parameters of a homogeneous Gaussian random field of a certain class. We find confidence ellipsoids for estimators of this sort.